Allegories of transgression and transformation : experimental fiction by women writing under dictatorship - Tierney-Tello, Mary Beth, 1961- (State University of New York Press, 1996)
"The Latin American dictatorships of the 1970s-80s (dirty wars against civilian population) coincided with the period of women's liberation. Vol. deals with incursion and participation of women in all levels of society, but especially in the literary-political sphere. Work is concerned with how women writers responded to these regimes in Chile, Argentina, Brazil, and Uruguay through the literature of Cristina Peri Rosi, Diamela Eltit, Nélida Piñon, and Reyna Roffé. Theoretically well grounded in feminist and political theory and extremely well written, this lucid book represents a breakthrough in women's studies and a welcome respite from the feminist canon which has overworked the texts of a small number of women writers. Recommended as a point of departure for new studies on women"--Handbook of Latin American Studies, v. 58.